2017
DOI: 10.1016/j.jss.2017.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Reverse engineering language product lines from existing DSL variants

Abstract: The use of domain-specific languages (DSLs) has become a successful technique to develop complex systems. In this context, an emerging phenomenon is the existence of DSL variants, which are different versions of a DSL adapted to specific purposes but that still share commonalities. In such a case, the challenge for language designers is to reuse, as much as possible, previously defined language constructs to narrow implementation from scratch. To overcome this challenge, recent research in software languages e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…DSLs can be modeled as a family of languages rather than stand-alone monolithic implementations when developed in a LPL fashion. For instance, several works (Tratt 2008;Crane and Dingel 2005;Vacchi et al 2013;Méndez-Acuña et al 2017) showed that the variants of state machine languages can be modeled as a single family of programming (Cazzola and Poletti 2010). Each sub-tree models the variability of a different language construct.…”
Section: Language Product Linesmentioning
confidence: 99%
“…DSLs can be modeled as a family of languages rather than stand-alone monolithic implementations when developed in a LPL fashion. For instance, several works (Tratt 2008;Crane and Dingel 2005;Vacchi et al 2013;Méndez-Acuña et al 2017) showed that the variants of state machine languages can be modeled as a single family of programming (Cazzola and Poletti 2010). Each sub-tree models the variability of a different language construct.…”
Section: Language Product Linesmentioning
confidence: 99%
“…An approach [49] is presented to extracting complex feature correlations from existing product configurations using association mining techniques. In [33] a reverse engineering technique is proposed to automatically build up language product lines from exiting DSL variants. [13] provides approach to mine a feature model based on the formal conceptual models and configurations.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, paper [15] proposed a feature-oriented approach to automatically mine legacy system models via comparing, matching and merging artifacts. Recently, [16] proposed an approach that reuses Domain Specific Languages models and synthesizes with the corresponding OVM variability model. K. Czarnecki et al [17] proposed a feature models mining method based on conjunctive and disjunctive association rule mining.…”
Section: A Current Advances In Splementioning
confidence: 99%